Pengaruh Kegiatan Keagamaan di Lingkungan Sekolah dan Keluarga dalam Membentuk Pengalaman Beragama - Ningtyas, Dea Tara; Saputera, Abdur Rahman Adi (Tapis: Jurnal Penelitian Ilmiah, 2018)
The mission of national education is to educate and shape the generation that has a good personality characteristic. This research was conducted in order to support the success of achieving above mission by investigating the influence of religious activities in the school and family environment in shaping the Islamic character of students. Muhammadiyah 2 Junior High School of Yogyakarta provides character and religious education with the programs integrated with learning inside and outside the classroom such as Tahsin Al-Quran, Tahfizh Al-Quran, and so forth. The implementations of religious activities are expected to influence the students’ religious experiences to become the expected character.